Prescribers' perspectives: The impact of the controlled substance scheduling system on providing optimal patient care - Michael R. Barnes; Yijia Luo; Jonathon M. Parker; Brian M. Shepler (Elsevier, 2024)
Background: In the United States, the scheduling system for controlled substances was established by the Controlled Substance Act of 1970. In 2009, Parker et al. published the study "Physicians' knowledge and attitudes toward scheduling." Since 2009, the opioid epidemic has gathered national attention from social and scientific perspectives as the number of drug overdose deaths in the United States has nearly tripled. Objective: To follow up on a 2009 survey by Parker, et al. to determine prescribers' knowledge and attitudes regarding the controlled substance scheduling system and assess the impact of the controlled substance scheduling system on providing optimal patient care. Methods: The cross-sectional survey was designed to assess prescribers' attitudes and mailed to 400 randomly selected physicians and 400 randomly selected nurse practitioners. Results: Prescribers across all groups provided consistent responses suggesting an overall lack of understanding of controlled substance regulations, a negative attitude towards the controlled substance scheduling system, and a detrimental effect on providing optimal patient care. Responses from nurse practitioners differed significantly from physicians in 75 % (3 of the 4) questions regarding regulations, suggesting nurse practitioners possess a greater understanding of pharmaceutical regulations. Specialists' responses demonstrated an enhanced level of dissatisfaction regarding the controlled substance scheduling system compared to primary care providers in 75 % (3 of the 4) questions. Questions regarding the impact of the scheduling system on prescribing patterns differed significantly across multiple demographic groups, notably between physicians and nurse practitioners, differences in practice setting, and primary state of practice for 75 % (3 of the 4) questions. Conclusions: The results of this survey confirm the findings of Parker, et al., and further display the need for investigation into how to improve the controlled substance scheduling system in the United States.